Implementation of Antiestablishment Wire Fault Sensing Using CC3200 - S Shanmugasundaram (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Underground cables are inclined to faults because of underground conditions. Detecting particular fault area in the underground cable is a tedious one for that the whole line is to be dug check and settle issues. The proposed method using IoT identifies the correct fault position that makes repairing work simple. The professional domain workers identify the fault area sometimes they also are not able to predict the fault location. Determining fault in the cable itself take lots of time, cash and endeavours and furthermore permit to service underground links speedier. An excellent Wi-Fi featured ARM Cortex-M4 microcontroller is utilised to implement the system. This device offers a total, ease, practical and easy to use method for continuous checking. The fault is acknowledged with the help of sensors placed over the cable. The cell phone application furnishes with a GUI to screen the information from a remote area. The cloud server act as the centre man between the hardware device and the cell phone application dealing with the data movement.